T-Shaped matched resonator bandstop filter for microwave applications - Ahmad, Badrul Hisham; Ramlan, Muhammad Zulfaqar; Zahari, Mohd Khairy; Hassan, Nornikman; Ab Rashid, Amier Hafizun (2024)
This research shows that there's a type of first-order network that can achieve perfect signal matching at all frequencies, complete stopband attenuation, and optimal resonance. To filter out noise or interference, the study introduces a T-shaped resonator bandstop filter. This filter is designed using Advanced Design System (ADS) software and built on a Rogers Duroid RT 5880 board. This board has a dielectric constant of 2.20, a high-quality factor (Q), a characteristic impedance of 50 ohms, a return loss of S11 < -10dB, and specific substrate thicknesses of 0.787 mm and 0.017 mm. The goal of this paper is to effectively separate the desired signal from interference at chosen frequencies in real-world situations.